Perkembangan islam di timur tengah: Pemikiran muhammad bin abdul wahab - Rahma, Resa Kurnia (Maliki Interdisciplinary Journal, 2025)
Muhammad bin Abdul Wahab is a renewal figure in Islamic theology, so it is important to know how the thoughts and schools founded by him. The goal is to create harmony and tolerance among Muslims and avoid sharp criticism or excommunicate fellow Muslims, because in fact the truth belongs only to Allah SWT, and Islam is a religion that loves peace. Muhammad bin Abdul Wahab's thoughts include adhering to the Qur'an and sunnah as the main sources of Islamic law, trying to improve the understanding of monotheism, inviting Muslims to return to practicing religion like the companions in the early days of Islam, and following the teachings of the righteous salaf and the mujtahid imams. In addition, it rejects fanaticism, and calls for da'wah based on correct evidence. His thinking also sought to eradicate heresy and false beliefs that arose from ignorance and backwardness.